IMPLEMENTASI KEBIJAKAN TATA CARA PENYELENGGARAAN CADANGAN PANGAN DAN MEWUJUDKAN KETAHANAN PANGAN DI KABUPATEN BANGLI - I Kadek Dede Junaedy; Ni Luh Putu Ening Permini; I Wayan Arya Sugiarta; I Made Artayasa; Ni Kadek Ariati; Ni Putu Manik Puryantini (Universitas Wijaya Kusuma Surabaya, 2026)
This study aims to provide an in-depth analysis of the implementation of food reserve management policies as part of efforts to achieve sustainable food security in Bangli Regency. This region was selected due to its mountainous geography with limited accessibility and a socioeconomic structure still dominated by subsistence agriculture, making it vulnerable to food supply disruptions due to natural factors and market dynamics. These conditions demand food reserve policies that are adaptive, responsive, and tailored to the local context. The study used a qualitative approach with a case study method to explore the role of local government, institutional capacity, obstacles, and strategies for implementing Bangli Regency Regulation Number 11 of 2022 concerning Food Reserve Management Procedures. Data were collected through in-depth interviews, field observations, and analysis of policy documents. The analysis utilized George C. Edwards III's framework, which emphasizes the importance of policy communication, resource availability, implementer disposition, and bureaucratic structure as determinants of implementation success. This framework is enriched with the perspectives of Mazmanian and Sabatier to understand the interrelationships between policy design, socio-political conditions, and implementer capacity. The research is expected to produce an empirical overview of policy implementation in Bangli, as well as theoretical and practical contributions to strengthening food reserve governance. The findings of this study are expected to serve as a reference for formulating more effective, participatory, and evidence-based policies, and can be replicated in other regions with similar characteristics.